Influence of breeding season on fecal glucocorticoid levels in captive Greater Rhea (Rhea americana) - Leche, Alvina (2015)
Sex hormones and stress-related changes can be seasonally influenced. We investigate whether fecal glucocorticoid metabolite (FGM) levels can differ between male and female captive Greater Rheas during the breeding and non-breeding seasons. Over a 3-year-period, fresh fecal samples from 10 individuals (five of each sex) were collected during the breeding months (October, November and December) and non-breeding months (April and June). A total of 960 samples were assayed using a commercial radioimmunoassay. Results showed that FGM levels (mean ± SE) were affected by the breeding season in a sex-dependent way. Male Greater Rheas showed significantly higher FGM levels in the breeding months than in the non-breeding months (13.44 ± 0.37 vs 7.92 ± 0.1 ng/g feces, respectively). By contrast, females did not show FGM seasonal changes throughout the same sampling periods (7.55 ± 0.14 vs 7.26 ± 0.73 ng/g feces). Moreover, during the breeding season months, males showed higher average FGM levels than females (13.44 ± 0.37 vs 7.55 ± 0.14 ng/g feces, respectively), and no differences were found between sexes during the non-breeding season (7.92 ± 0.1 vs 7.26 ± 0.73 ng/g feces, respectively). Our findings suggest that male Greater Rheas have a higher adrenocortical activity during the breeding season, which is probably indirectly related to the increased testosterone levels and agonist interactions that are also observed during that phase. Studies aimed to determine the appropriate sex ratio for captive rearing should be developed to minimize male agonist encounters and therefore improve welfare of the captive group.